Pengaruh Layanan Informasi Karier Menggunakan Media Portofolio Terhadap Pengambilan Keputusan Studi Lanjut Siswa di SMAN 1 Bantaeng - Manippi, Ibnu Hajar; Pandang, Abdullah; Buchori, Sahril (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Lack of information about further studies for high school students after graduation is a significant problem in their study selection. This can hinder students' ability to make informed educational choices that align with their interests and goals. The formulation of the problem in this research is whether there is an influence of information services using portfolio media on students' decision making for further studies at SMAN 1 Bantaeng. This research aims to determine the significant influence of career information services using portfolio media on students' further study decisions at SMAN 1 Bantaeng. This research is a quasi-experimental type using pretest-posttest, non-equivalent control group design. Research participants were class XII MIPA 4 students at SMAN 1 Bantaeng. There were 20 participants in this study and were divided into two groups, namely the experimental group (N=10) and the control group (N=10). The measuring instrument used in this research was a questionnaire for selecting students for further studies. The data analysis technique uses independent sample t-test hypothesis testing. The research results show that information services using portfolio media can increase students' further study decision making scores at SMAN 1 Bantaeng. The results of the independent sample t-test are p = 0.000 0.05, then Ho is rejected and Ha is accepted so it can be concluded that there is an influence of career information services using portfolio media on students' further study decisions at SMAN 1 Bantaeng. The implication of this research is that portfolios can be used as a medium to improve high school students' decision making for further studies.